Developing positive emotions by listening to Islamic talks on the Internet - Fontaine, Rodrigue Ancelot Harvey (2011)
This study explores the ‘broaden-and-build’ theory of positive emotions (Cohn & Frederickson, 2009) with students at the International Islamic University Malaysia (IIUM). 206 students from IIUM taking management courses completed an assignment in which they had to listen to one Islamic talk on the Internet a week for at least 12 weeks. This author created a blog with links to good Islamic websites. For control purposes, students could only access the sites linked to the blog. At the end of the semester, students submitted their reflections. The quantitative data shows that 80% of respondents developed positive outcomes. The qualitative data shows that students seem to deal with personal difficulties in a more constructive way. Seeking answers to questions they have about Islam and re connecting with the Qur’an were two recurring themes in the respondents’ reports. This author speculates that an Islamic version of ABCD can be devised. The results, the implications and the limitations of this study are discussed.